ASSESSING THE EFFECTIVENESS OF THE ’PROGRAM CANTAS GAGAL’ ON REDUCING FAILURE RATES IN SOLID MECHANICS - Nor Hafida Hashim; Muhamad Faizal Pakir Mohamed Latiff; Mohd Zaini Endut; Hasbullah Hashim; Nik Farhanim Imran; Daliah Hasan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Improving student performance in challenging subjects like Solid Mechanics requires innovative intervention strategies. This study evaluates the effectiveness of the "Program Cantas Gagal," a targeted remedial program implemented at UiTM Pulau Pinang to reduce the failure rate in Solid Mechanics for Diploma Civil Engineering students. The program involves conducting multiple extra classes where past year exam questions are extensively discussed with students. The problem addressed is the high failure rate observed in previous semesters, particularly a 20% failure rate in semester 20232. In response, the "Program Cantas Gagal" was introduced in semester 20234, aimed at providing students with additional support and focused revision sessions. The objective of this study is to assess the impact of this program on reducing the failure rate and improving overall student performance. Methodologically, this research involves a comparative analysis of failure rates and student grades from semester 20232 and semester 20234. Results show a significant reduction in the failure rate, from 20% in semester 20232 to 6% in semester 20234, indicating the program’s effectiveness. The discussion highlights how the additional classes and focused discussions on past exam questions have contributed to a better understanding and application of the course material by the students. In conclusion, the "Program Cantas Gagal" has proven to be an effective strategy in improving student performance in Solid Mechanics. This study contributes valuable insights into educational intervention programs, demonstrating that targeted remedial actions can substantially enhance student outcomes in engineering education.